EML4–NTRK3 Fusion Cervical Sarcoma: A Case Report and Literature Review - Dang, Xiaohe; Xiang, Tao; Zhao, Can; Tang, Hao; Cui, Pengfei (Frontiers in Medicine, 2022)
The concept of neurotrophic factor tyrosine kinase receptor (NTRK) fusion tumor has emerged in recent years. Moreover, NTRK fusion is unusual in common tumors but can often be identified in rare tumors. The NTRK fusion cervical or uterine tumors are mainly recognized through case reports due to their extremely low incidence. In this study, we reported a new case of EML4–NTRK3 fusion cervical sarcoma to enhance its recognition. To the best of our knowledge, this is the first case from a Chinese institution. We also conducted a literature review, in which a total of 19 cases of NTRK fusion cervical tumors and 4 cases of uterine tumors were retrieved. We summarized the clinicopathological features, treatment methods, and prognosis of these cases. Based on available information, we observed that surgery and complete excision, if possible, are still the primary modes of therapy. In addition, an increasing number of studies have shown that tropomyosin receptor kinases (TRK) inhibitors can improve the prognosis of cancer patients with NTRK gene fusion, which gives a silver lining for patients with metastatic lesions. We found that age and mitotic rate may be associated with recurrence or metastasis by univariate survival analysis. To draw more convincing conclusions, there is a need to establish an international database of rare cases and aggregate these sporadic cases.